2004
DOI: 10.1074/jbc.m406323200
|View full text |Cite
|
Sign up to set email alerts
|

Osmolytes Induce Structure in an Early Intermediate on the Folding Pathway of Barstar

Abstract: Osmolytes stabilize proteins against denaturation, but little is known about how their stabilizing effect might affect a protein folding pathway. Here, we report the effects of the osmolytes, trimethylamine-N-oxide, and sarcosine on the stability of the native state of barstar as well as on the structural heterogeneity of an early intermediate ensemble, I E , on its folding pathway. Both osmolytes increase the stability of the native protein to a similar extent, with stability increasing linearly with osmolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 59 publications
6
79
0
Order By: Relevance
“…The extracted m values for all these osmolytes vary only moderately for protein L (m ϭ Ϫ(0.1 to 0.2) kcal mol Ϫ1 M Ϫ1 ) and for CspTm (m ϭ Ϫ(0.5 to 0.3) kcal mol Ϫ1 M Ϫ1 ; see Table 1). The nearly constant m values for the osmolytes is consistent with experiments that have found that m values for TMAO and sarcosine are roughly the same for barstar (39). As a result of the small m values the osmolytes increase the stability of the small proteins only modestly (Ϸ1 kcal/mol).…”
Section: Measured and Predicted Fret Efficiencies Are In Good Agreementsupporting
confidence: 75%
“…The extracted m values for all these osmolytes vary only moderately for protein L (m ϭ Ϫ(0.1 to 0.2) kcal mol Ϫ1 M Ϫ1 ) and for CspTm (m ϭ Ϫ(0.5 to 0.3) kcal mol Ϫ1 M Ϫ1 ; see Table 1). The nearly constant m values for the osmolytes is consistent with experiments that have found that m values for TMAO and sarcosine are roughly the same for barstar (39). As a result of the small m values the osmolytes increase the stability of the small proteins only modestly (Ϸ1 kcal/mol).…”
Section: Measured and Predicted Fret Efficiencies Are In Good Agreementsupporting
confidence: 75%
“…3 a and b), indicating that the polypeptide chain does not encounter a sizeable free energy barrier while folding to I E . This interpretation gains credence from several earlier observations: (i) the structure of I E is different in the presence of different osmolytes and different salts (25,26); (ii) different intramolecular distances in I E contract in a gradual and asynchronous manner, upon a reduction in denaturant concentration (9); (iii) the free energy difference between U and I E turns out to be less than k B T (25,26) if the U-to-I E transition is assumed to be barrier-limited; (iv) I E is loosely packed throughout its structure (33) and hence is expected to form with a lack of cooperativity (20,34); and (v) most importantly, gradual structural changes in the folded as well as unfolded forms of barstar have been detected in equilibrium unfolding studies (12,13).…”
Section: Absence Of a Significant Free Energy Barrier During The Sub-msmentioning
confidence: 66%
“…Far-UV CD and fluorescence measurements in the millisecond time domain were done by using a Biologic SFM-4 module, as described previously (8,9,26).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations